The University Services and the Performances of Music, Arts, Physical Education and Health (MAPEH) Graduates in the Licensure Examination for - Samonte, Kenneth (JPAIR Institutional Research, 2017)
One significant component to assure the quality of teaching workforce in most states is the Licensure Examination. The performance of education graduates in the licensure examination for teachers may also serve as an evaluation of the quality of education which the College of Education offers to its students. The study aimed to determine the performance of Music, Arts, Physical Education, and Health (MAPEH) graduates in the Licensure Examination for Teachers (LET) and if there is an existing relationship between the LET performance and the different contributory factors, namely; subjects (general education, professional education, and field of specialization), facilities, administrative management and program/activities. Eighty-four (84) BSE MAPEH major graduates served as respondents. The descriptive correlational method specifically questionnaires served as the primary tool for data gathering, and it was supplemented by interviews, with the mean and Pearson Product Moment (PPM). The findings revealed that most of the respondents failed in Professional Education and passed in the Field of Specialization and General Education subjects. It was found out that gender is significantly related to LET performance of the respondents and that there was no significant relationship existed between the respondents’ LET performance and the different contributory factors, namely, Subjects, Facilities, Administrative Management and Program/Activities.